2005
DOI: 10.1148/radiol.2363041080
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Acute Renal Transplant Rejection with Blood Oxygen Level–Dependent MR Imaging: Initial Experience

Abstract: R2* measurements in the medullary regions of transplanted kidneys with acute rejection were significantly lower than those in normally functioning transplants or transplants with ATN. These results suggest that marked changes in intrarenal oxygenation occur during acute transplant rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(92 citation statements)
references
References 25 publications
7
84
1
Order By: Relevance
“…Sadowski and coworkers reported BOLD MRI measurements in kidney allografts with ATN (n=4-6) within 4 months post-transplantation. [64][65][66] There was no significant difference in cortical oxygenation in the ATN group compared with normal functioning allografts, although one study showed a trend toward cortical hypoxia. Medullary oxygenation was significantly increased in the ATN group in one study, but not in the other two.…”
Section: Acute Tubular Necrosismentioning
confidence: 94%
See 1 more Smart Citation
“…Sadowski and coworkers reported BOLD MRI measurements in kidney allografts with ATN (n=4-6) within 4 months post-transplantation. [64][65][66] There was no significant difference in cortical oxygenation in the ATN group compared with normal functioning allografts, although one study showed a trend toward cortical hypoxia. Medullary oxygenation was significantly increased in the ATN group in one study, but not in the other two.…”
Section: Acute Tubular Necrosismentioning
confidence: 94%
“…[64][65][66][67]79,80 In three separate publications, Djamali et al 64 and Sadowski et al 65,66 found that within the first 4 months after renal transplantation, acute rejection (n=8-13) was associated with increased renal medullary oxygenation, despite reduced medullary blood flow, as compared with both normally functioning allografts and allografts with ATN. Cortical oxygenation was similar in all groups.…”
Section: Kidney Transplantationmentioning
confidence: 99%
“…There have been studies using blood oxygenation level-dependent magnetic resonance imaging in experimental ischemic AKI and clinical settings, including allograft rejection compared with normal functional transplants and transplants with acute tubular necrosis. [9][10][11] Other noninvasive tools that are potential candidates for assessing RBF and tissue oxygenation include positron emission tomography and optical spectroscopy, 12,13 both of which need validation in additional clinical studies.…”
Section: Methodsmentioning
confidence: 99%
“…6) may be an indicator of acute rejection. Further support for this consideration comes from the finding that functional T2-mapping (BOLD) MRI has been shown to differentiate ATN and acute rejection (27,57).…”
Section: Acute Rejectionmentioning
confidence: 99%